2017
DOI: 10.1111/1751-7915.12687
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectroventing: an electrochemical‐assisted bioremediation strategy for cleaning‐up atrazine‐polluted soils

Abstract: SummaryThe absence of suitable terminal electron acceptors (TEA) in soil might limit the oxidative metabolism of environmental microbial populations. Bioelectroventing is a bioelectrochemical strategy that aims to enhance the biodegradation of a pollutant in the environment by overcoming the electron acceptor limitation and maximizing metabolic oxidation. Microbial electroremediating cells (MERCs) are devices that can perform such a bioelectroventing. We also report an overall profile of the 14C‐ATR metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Following a similar strategy, toxicity reduction instead of full oxidation, METs have been used for azo dye orange 7 reduction into sulfanilic acid (Yun et al ., ) and the toxicity of waters containing dibenzothiophene or atrazine has also been decreased (Rodrigo et al ., ; Domínguez‐Garay et al ., ). Atrazine is an interesting example, as it has been successfully mineralized (Domínguez‐Garay et al ., ). This example shows the potential of METs over the treatment of complex aromatic compounds.…”
Section: Organic Contaminantsmentioning
confidence: 97%
“…Following a similar strategy, toxicity reduction instead of full oxidation, METs have been used for azo dye orange 7 reduction into sulfanilic acid (Yun et al ., ) and the toxicity of waters containing dibenzothiophene or atrazine has also been decreased (Rodrigo et al ., ; Domínguez‐Garay et al ., ). Atrazine is an interesting example, as it has been successfully mineralized (Domínguez‐Garay et al ., ). This example shows the potential of METs over the treatment of complex aromatic compounds.…”
Section: Organic Contaminantsmentioning
confidence: 97%
“…Negative potentials as low as −400 mV are typically reached in anodes buried in flooded environments due to the anoxic nature of the environment [27,29]. Although such a condition already enhanced the microbial activity, some authors have additionally reported higher bioremediation rates under a more positive anode potential by using a potentiostat as a tool for polarizing the electrode [37,28]. An electron acceptor with a higher redox potential is consistent with having a higher cell growth yield and harvesting more electrical current.…”
Section: Enhanced Smz Mineralization By Using Mercmentioning
confidence: 99%
“…Likewise, these microorganisms can also use electrodes as electron source for reducing pollutants [23]. They have demonstrated efficient removal of nutrients such as nitrates [22], chlorinated hydrocarbons [24], antibiotics [25,26], herbicides [27][28][29], and petroleum hydrocarbons [30,31]. Furthermore, microbial electrochemistry in combination with the anaerobic digestion of livestock manures has already been used to simultaneously generate electricity, remove organic matter and recover nitrogen [31][32][33][34], while eliminating unpleasant odors [35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, based on the inexhaustible electron acceptor of the solid anode, the enhancement ability of the biocurrent is sustained, which overcomes the deciency of the electron acceptor in a contaminated medium. 16,17 However, there are still some problems to be solved in the actual application of BESs, such as improving the degradation of complex compounds, controlling the reaction process of microorganisms, and continuing to reduce costs.…”
Section: Introductionmentioning
confidence: 99%